A novel EPID design for enhanced contrast and detective quantum efficiency. (5th August 2016) - Rottmann, Joerg; Morf, Daniel; Fueglistaller, Rony; Zentai, George; Star-Lack, Josh; Berbeco, Ross
Abstract: Beams-eye-view imaging applications such as real-time soft-tissue motion estimation are hindered by the inherently low image contrast of electronic portal imaging devices (EPID) currently available for clinical use. We introduce and characterize a novel EPID design that provides substantially increased detective quantum efficiency (DQE), contrast-to-noise ratio (CNR) and sensitivity without degradation in spatial resolution. The prototype design features a stack of four conventional EPID layers combined with low noise integrated readout electronics. Each layer consists of a copper plate, a scintillator ( G d 2 O 2 S : T b ) and a photodiode/TFT-switch (aSi:H). We characterize the prototype's signal response to a 6 MV photon beam in terms of modulation transfer function (MTF), DQE and CNR. The presampled MTF is estimated using a slanted slit technique, the DQE is calculated from measured normalized noise power spectra (nNPS) and the MTF and CNR is estimated using a Las Vegas contrast phantom. The prototype has been designed and built to be interchangeable with the current clinical EPID on the Varian TrueBeam platform (AS-1200) in terms of size and data output specifications. Performance evaluation is conducted in absolute values as well as in relative terms using the Varian AS-1200 EPID as a reference detector. A fivefold increase of DQE(0) to about 6.7% was observed by using the four-layered design versus the AS-1200 reference detector. No substantial differences are observed between each layer's individual MTF and the one for all four layers operating combined indicating that defocusing due to beam divergence is negligible. Also, using four layers instead of one increases the signal to noise ratio by a factor of 1.7.